Beginning Java Google App Engine - Roche, Kyle (Apress, 2012)
Application development, as you know it, is about to change. Think about your development project plans for a moment. Do they all seem to have the same line items for the first phase? Build a server. Install a database. Configure the application server. You’re a programmer, aren’t you? Why spread your talents so thin? You should be able to focus your energy on building the application from day one. That’s where Google App Engine comes into the picture. There’s no need to ever worry about building a development server, installing a database, setting up an application server, opening ports, and the endless other tasks that come with traditional development. With Google App Engine, you can start building your application right away. Google App Engine applications are built using the same tools you use today for Java development. The Google Plugin for Eclipse allows you to develop your entire application in a single IDE. Everything from data management to user-interface design is encompassed in the development environment. You no longer need to use a different tool or server for each layer of the application stack. And most importantly, it’s an unquestionable advantage to be able to spend less time on setting up the evironment and more time on the application's business value.